Blood lipids, lipid-regulatory medications, and risk of bladder cancer: a Mendelian randomization study - Cheng, Zhang; Ye, Fangdie; Liang, Yingchun; Xu, Chenyang; Zhang, Zheyu; Ou, Yuxi; Chen, Xinan; Dai, Xiyu; Mou, Zezhong; Li, Weijian; Chen, Yiling; Zhou, Quan; et al. (Frontiers in Nutrition, 2023)
Background: The influences of blood lipids and lipid-regulatory medications on the risk of bladder cancer have long been suspected and previous findings remain controversial. We aimed to assess the causality between blood lipids or lipid-regulatory medications and bladder cancer susceptibility by means of a comprehensive Mendelian Randomization (MR) study. Methods: Genetic proxies from genome-wide association studies (GWAS) of four blood lipids traits and lipid-lowering variants in genes encoding the targets of lipid-regulatory medications were employed. The largest ever GWAS data of blood lipids and bladder cancer involving up to 440,546 and 205,771 individuals from European ancestry were extracted from UK Biobank and FinnGen Project Round 6, respectively. A two-sample bidirectional MR study was performed using the inverse variance weighted as the main method. The heterogeneity, horizontal pleiotropy, MR Steiger, leave-one-out analyses were also conducted as sensitivity tests. Results: There was indicative of evidence that genetically predicted low-density lipoprotein cholesterol (LDL-C) affected bladder cancer susceptibility based on 146 single nucleotide polymorphisms (SNPs) with an odds ratio (OR) of 0.776 (95% confidence interval [CI] = 0.625-0.965, P = 0.022). However, the result became non-significant after two SNPs that possibly drove the effect as demonstrated by leave-one-out analysis were removed. The reversed MR analysis suggested that bladder cancer could not affect serum lipids level. No causal relationship was found between lipid-lowering effect of lipid-regulatory medications (fibrates, probucol, statins, ezetimibe, Proprotein convertase subtilisin/kexin type 9 [PCSK9] inhibitors, and evinacumab) with the risk of bladder cancer. No heterogeneity or pleiotropy was found (all P > 0.05). Conclusions: Using the latest and largest GWAS data to date, this MR study disclosed for the first time that genetically predicted total cholesterol (TC) and lipid-lowering effect of lipid-regulatory medications had no causal association with bladder cancer susceptibility, and we ascertained that low-density lipoprotein cholesterol (HDL-C), LDL-C, and triglyceride (TG) are not related with bladder cancer susceptibility either. The current study indicated that lipid metabolism may not be as important in the tumorigenesis of bladder cancer as previously believed.